Inequalities in maternity care and newborn outcomes: one-year surveillance of births in vulnerable slum communities in Mumbai - More Neena; Bapat Ujwala; Das Sushmita; Barnett Sarah; Costello Anthony; Fernandez Armida; Osrin David (BMC, 2009)
Abstract Background Aggregate urban health statistics mask inequalities. We described maternity care in vulnerable slum communities in Mumbai, and examined differences in care and outcomes between more and less deprived groups. Methods We collected information through a birth surveillance system covering a population of over 280 000 in 48 vulnerable slum localities. Resident women identified births in their own localities and mothers and families were interviewed at 6 weeks after delivery. We analysed data on 5687 births over one year to September 2006. Socioeconomic status was classified using quartiles of standardized asset scores. Results Women in higher socioeconomic quartile groups were less likely to have married and conceived in their teens (Odds ratio 0.74, 95% confidence interval 0.69-0.79, and 0.82, 0.78-0.87, respectively). There was a socioeconomic gradient away from public sector maternity care with increasing socioeconomic status (0.75, 0.70-0.79 for antenatal care and 0.66, 0.61-0.71 for institutional delivery). Women in the least poor group were five times less likely to deliver at home (0.17, 0.10-0.27) as women in the poorest group and about four times less likely to deliver in the public sector (0.27, 0.21-0.35). Rising socioeconomic status was associated with a lower prevalence of low birth weight (0.91, 0.85-0.97). Stillbirth rates did not vary, but neonatal mortality rates fell non-significantly as socioeconomic status increased (0.88, 0.71-1.08). Conclusion Analyses of this type have usually been applied across the population spectrum from richest to poorest, and we were struck by the regularly stepped picture of inequalities within the urban poor, a group that might inadvertently be considered relatively homogeneous. The poorest slum residents are more dependent upon public sector health care, but the regular progression towards the private sector raises questions about its quality and regulation. It also underlines the need for healthcare provision strategies to take account of both sectors.